The Skills Road : Skills for Employability in Tajikistan - Ajwad, Mohamed Ihsan; Hut, Stefan; Abdulloev, Ilhom; Audy, Robin; de Laat, Joost; Kataoka, Sachiko; Larrison, Jennica; Nikoloski, Zlatko; Torracchi, Federico (World Bank, Washington, DC, 2014)
This report addresses a fundamental question facing policy makers in Tajikistan: is the current level of worker skills hindering employment outcomes? Using a unique household survey, the study finds that skills are valued in Tajikistan’s labor market, yet skills gaps persist. Jobs have been created in more knowledge-intensive occupations and in the service sector as opposed to the more traditional manual jobs, and employment outcomes are stronger for workers with better skills. Analysis of worker skills shows that workers with better cognitive and non-cognitive skills are typically more likely to have the highly sought-after formal sector jobs; and in fact make more frequent and intense use of mathematics and reading skills on the job. Furthermore, workers with better non-cognitive skills tend to become supervisors. The study finds that there are large variations in observed skills among those with the same level of educational attainment, indicating that formal education is failing too many people even though skills are developed during different stages in the life cycle and a host of actors are involved—families, for example, play a central role. The report’s conclusion is that the government could shift the focus from providing access to educational institutions and instead focus on providing the skills (cognitive, non-cognitive, and technical) students need to succeed as adults. The government can also do more to get children off to the right start by investing in early childhood development programs, where rates of return to investment are generally very high and important soft skills are learned. Finally, more can be done to match worker skills with employer demand by improving the use of information in matching skills to jobs in the labor market.